2010
DOI: 10.1590/s0100-204x2010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Software for interpolation of vegetative growth of yerba mate plants in 3D

Abstract: -The objective of this work was to build mock-ups of complete yerba mate plants in several stages of development, using the InterpolMate software, and to compute photosynthesis on the interpolated structure. The mock-ups of yerba-mate were first built in the VPlants software for three growth stages. Male and female plants grown in two contrasting environments (monoculture and forest understory) were considered. To model the dynamic 3D architecture of yerba-mate plants during the biennial growth interval betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The biennial growth of yerba-mate plants cultivated in MO was influenced strongly by GDD in males, while NL affected growth parameters of both genders, and strongly influenced the leafy axis growth even in an environment more like the yerba-mate's natural habitat (FUS). The crucial role of the cultivation system in the modification of yerba-mate production (Rakocevic et al 2006c), leaf and plant photosynthesis, and sexual dimorphism has been demonstrated (Silva and Rakocevic 2010). Yerba-mate growth modifications affected by environment were much more pronounced when plants were grown in a cultivation system that is less like the yerba-mate's natural habitat (MO) compared to those grown under FUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biennial growth of yerba-mate plants cultivated in MO was influenced strongly by GDD in males, while NL affected growth parameters of both genders, and strongly influenced the leafy axis growth even in an environment more like the yerba-mate's natural habitat (FUS). The crucial role of the cultivation system in the modification of yerba-mate production (Rakocevic et al 2006c), leaf and plant photosynthesis, and sexual dimorphism has been demonstrated (Silva and Rakocevic 2010). Yerba-mate growth modifications affected by environment were much more pronounced when plants were grown in a cultivation system that is less like the yerba-mate's natural habitat (MO) compared to those grown under FUS.…”
Section: Discussionmentioning
confidence: 99%
“…Adult yerba-mate plants respond strongly to high-light conditions (monoculture), where they show more intensive leaf emission and leaf area formation than when grown under the forest understorey (FUS; Rakocevic et al 2006a). Yerbamate leaf physiology changes when plants are grown in monoculture (Rakocevic et al 2009;Silva and Rakocevic 2010), and this strongly affects the characteristics of obtained 'chimarrão' (Rakocevic et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of yerba-mate SSD initiated with gender segregation in leaf gas exchanges (Rakocevic et al, 2007a(Rakocevic et al, , 2009, leaf chemical composition (Pauli et al, 2019;Rakocevic et al, 2007b;Tormena et al, 2020), beverage sensorial quality (Rakocevic et al, 2008a), plant growth, and architecture (Guédon et al, 2018;Matsunaga et al, 2014;Rakocevic et al, 2008b;Silva and Rakocevic, 2010). Biomass production does not differ between two genders (Rakocevic et al, 2007b), regardless of the system of yerba-mate cultivation, monoculture (full sunlight cultivation), or agroforestry production under shaded conditions (Matsunaga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SSD in leaf area and light interception are related to leaves positioned in the lowest plant layers . However, sexual responses strongly depend on the environment, especially light conditions, with some opposite effects observed in female and male plants (internode length and individual leaf size), according to whether they were cultivated in MO or in AFS, under high-or lowlight conditions, respectively (Rakocevic et al, 2008;Rakocevic & Martim, 2011;Silva & Rakocevic, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SSD in leaf area and light interception are related to leaves positioned in the lowest plant layers (Rakocevic et al, 2011). However, sexual responses strongly depend on the environment, especially light conditions, with some opposite effects observed in female and male plants (internode length and individual leaf size), according to whether they were cultivated in MO or in AFS, under high‐ or low‐light conditions, respectively (Rakocevic et al, 2008; Rakocevic et al, 2011; Rakocevic & Martim, 2011; Silva & Rakocevic, 2010). Optimized foliage structure and physiology in females are found to compensate for greater reproductive costs in early developmental stages in one yerba‐mate native population, but females and males were similar in terms of photosynthetic efficiency after 2‐years of regrowth (Rakocevic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%